Exploring Students' Common Errors in Writing Recount Texts: A Case Study at Junior High School - Yahrif, Muhamad; Sirajuddin, Suharti; Dahniar (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Writing recount texts remains a challenging task for many junior high school students in Indonesia, particularly because it requires an accurate use of grammar, sentence organization, and vocabulary mastery. Previous studies have shown that learners frequently commit errors in tense usage, sentence structure, and word choice, yet limited research has connected these issues to students’ dependency on translation tools and their overall writing competence. This study, therefore, aimed to explore the common errors made by eighth-grade students in writing recount texts and to identify the underlying causes of those errors. The research involved 25 eighth-grade students at SMP Negeri 1 Liliriaje, Soppeng, and data were collected through students’ written tasks supported by semi-structured interviews with both students and their English teacher. Employing a qualitative descriptive approach, data were collected through students’ written tasks and supported by interviews with both students and their English teacher. The analysis revealed four dominant error categories: verb tense misuse, subject–verb agreement errors, sentence structure problems, and spelling mistakes. Among these, verb tense errors—especially the inappropriate use of the present tense instead of the past tense—emerged as the most frequent, indicating students’ limited mastery of narrative conventions. In addition, interviews showed that students’ reliance on Google Translate contributed significantly to structural inaccuracies and hindered their grammatical development. The findings contribute to the field of English language teaching by highlighting the urgent need for explicit grammar instruction, vocabulary enrichment strategies, and guided use of translation technology. Pedagogically, this research offers insights into designing targeted writing instruction that addresses students’ recurring difficulties and fosters greater writing accuracy and independence in EFL contexts.